Maternal cytotoxic T cell responses to fetal antigens develop during human pregnancy and exhibit functional capacity in vitro. (7th June 2011) - Lissauer, D; Goodyear, O; Moss, P A H; Kilby, M D
Abstract : During pregnancy there is the transplacental 'traffic' of allogenic fetal cells into the maternal circulation and this could provoke a maternal cellular immune response. Transgenic murine models suggest during pregnancy cytotoxic T cells (CTL) specific for fetal antigen are deleted or rendered anergic. We investigated the maternal cellular immune response to fetal (HY) antigens during human pregnancy. Pregnant women without medical complications (n=90) were studied longitudinally prenatally and within the puerperium at 6 timepoints and non-pregnant multiparous controls (n=65) investigated. We used human leucocyte antigen-peptide (HLA) 'dextramers' in mothers who were HLA-A*0201 or HLA-B*0702 to detect fetal specific T cells; directly 'ex-vivo' with phenotyping of fetal-specific cells by 9 colour flow cytometry and following expansion in culture. Fetal specific CTL were cloned and functional assessment performed. Maternal CTL responses against fetal antigen were detected in 51% of multiparous women (14/27), even decades after pregnancy. Such responses were also detected prenatally in 54% (18/33) of women. T cell clones specific for fetal cells were isolated from maternal blood during pregnancy and the puerperium (n=16). Fetal-specific clones are cytotoxic (>50% killing at a 1:1 ratio) and release IFN-α (mean 1600 pg/ml IFN-α) in response to fetal antigen, with no difference in function between clones isolated prenatally or after pregnancy. A maternal cellular immune responses to fetal antigens can commonly be detected during and after human pregnancy. Functional investigations demonstrated that they retain cytotoxicity and their ability to produce cytokines. This novel finding has important implications for understanding the immunobiology of pregnancy, spontaneous abortion and transplantation.